DISIPLIN, ETOS KERJA DAN IKLIM ORGANISASI DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN KABUPATEN KUBU RAYA - Amelia Amelia; Juliahir Barata; Udin Rinaldi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2018)
The research objective is to investigate and analyze the influence of work discipline, work ethic and organizational climate on the performance of employees at the Department of Agriculture Kubu Raya, either partially or simultaneously. The study used survey methods in an attempt to gather more field data assisted with research instruments adapted to the characteristics of descriptive qualitative research, in this case the researchers provide questionnaires/interview guides are adjusted to the dimensions of the study variables. Based on the research results, simultaneously (Test F) accept the hypothesis of the influence of variables work discipline, work ethic and organizational climate on employee performance Kubu Raya District Agricultural Office. Dominance partially on the performance of successively more influenced by variables discipline, work ethic and organizational climate.